Impact of wet work on epidermal barrier (TEWL and stratum corneum hydration) and skin viscoelasticity in nurses - Marta Kieć-Świerczyńska; Dorota Chomiczewska-Skóra; Dominika Świerczyńska-Machura; Beata Kręcisz (Nofer Institute of Occupational Medicine, 2014)
Background: Nurses are prone to develop hand eczema due to occupational exposure to irritants, including wet work. The aim of the study was to evaluate the impact of wet work on selected skin properties, reflecting epidermal barrier function - transepidermal water loss (TEWL) and stratum corneum hydration - and additionally skin viscoelasticity, in nurses. Material and Methods: Study subjects included 90 nurses employed in hospital wards. Measurements were carried out within the dorsal aspect of the dominant hand, using a Cutometer MPA 580 equipped with Tewameter TM 300 and Corneometer CM 825 (Courage&Khazaka, Germany) probes. Examinations took place on hospital premises. Similar measurements were performed in the control group of females non-exposed to irritants. Results: In the examined group of nurses, mean TEWL was 15.5 g/h/m2 and was higher than in the control group (12.99 g/h/m2). After rejecting the extreme results, the difference between the groups proved to be statistically significant (p < 0.05). The mean value of stratum corneum hydration was lower in the examined group (37.915) compared with the control group (40.05), but the difference was not statistically significant. Also results of viscoelasticity assessment showed no significant differences between studied groups. Conclusions: The results of the assessment of skin biophysical properties show that wet work exerts a moderately adverse impact on skin condition. A higher TEWL value and a lower stratum corneum hydration in workers exposed to irritants reflect an adverse impact of these factors on the epidermal barrier function. Med Pr 2014;65(5):609-619